ТАЪЛИМ ТИЗИМИНИ РИВОЖЛАНТИРИШДА ИҚТИСОДИЁТ СОҲАСИНИНГ ЎРНИ ВА РОЛИ - Tojiboyeva, Nargiza (FILOLOGIYA UFQLARI JURNALI, 2021)
The article provides information on education and science? Focusing on their aspects directly releted to the field of economics. The article also discusses the “Uzbek model” of development and human interests, human development in production, intellectual potential, human activity in social relations.